(untitled) - Whitlatch, E. Earl (New Jersey, 1997)
This text is unique in its presentation of civil and environmental engineering system from three perspectives. Modeling technologies presented in detail include linear and discrete optimization, modeling with multiple objectives, dynamic and nonlinear models, simulation and decision theory. Engineering economy is covered with chapters on interest and equivalence, investment decision making, and fiscal management including personal financial planning.
Keywords: Civil engineering,Environmental engineering,System analysis; Linear programming,Linear programming,Data processing